BUPIS UNTUK MEWUJUDKAN GERAKAN LITERASI SEKOLAH MENYONGSONG GERNAS BAKU PADA GUGUS DAHLIA KECAMATAN PARAKAN KABUPATEN TEMANGGUNG TAHUN 2018 - Asiyah, Siti (Widya Wacana: Jurnal Ilmiah, 2019)
Books are important world windows in human life. However, receiving a book that is only considered as something normal is not necessary if it is not read. Reading is very important for everyone. By reading, science will increase and be able to increase knowledge and insight. However, this reading activity has not been done much, especially for students. The benefits of reading for early childhood can add vocabulary, train children's memory, practice coordination, train child safety, develop children's interests, gather interest in reading children, recognize simple writing, recognize and understand letters, add child words, communicate quickly. The expected goal in the development of Bupis is to realize the School Literacy Movement to welcome Baku Gernas in Dahlia Cluster, Parakan District, Temanggung Regency. After Bupis development activities were carried out, the results of the teacher's skills showed the percentage of the suitability of the contents of the reading with the theme before the action was carried out by 65.7% can be increased to 80.7% after guidance was carried out. On other indicators, namely word selection of 69.4% increased to 77.8%. While the results of observations of children's reading interest in the indicator of children taking time to read every day increased from 61.4% to 85.7%, and indicators of pleasure when reading increased from 57.8% to 100%. Based on the description in the discussion, it can be concluded that the development of Bupis can improve teacher skills and increase children's reading interest. The teacher who initially did not have the skills in making Bupis, with guidance that supports the teacher is able to improve skills in making Bupis in accordance with the theme of learning in PAUD institutions, the choice of words in making Bupis is also adjusted to the development budget by the child. The skills of teachers in developing Bupis with indicators averaged 79.25%. Development of Bupis can also increase children's reading interest. Children who originally did not have the interest to read because of the absence of library facilities and other sources of information, with the existence of Bupis children's reading interest can be supported by an average indicator of 92.85%.Â Key words: Bupis, Literasi, Gernas Baku